In Vitro Testing In The Past Fluoride Ion Translucent Skin Mice Fluoride Via Skin Penetration Power Mouse (Transport Test In Vitro) - Aning Susilowati; Endah Aryati; Triwiyatini Triwiyatini (Jurnal Riset Kesehatan, 2012)
Aim of this research is to find out  if NaF solution and NaF solution added by enhancer can absorb mouse skin and transport timeconcentration which absorb mouse skin.  Research approach was experimental with Post test only group design. Research population and sample was fluoride concentration counted on resipent solution after transport test. Transport test using Franz Like Diffusion Cell with mouse skin as membrane, with NaF solution (group I) ; NaF solution added oleic acid as chemical enhancer (Group II) ; oleaic acid as control group (Group III) and CMF PBS 0,1 M pH  7,4 as donor solution and receptor solution. Interval time of transport test was 1, 4, 8, 12, 24 hours. Every time transport, sample was taken and fluoride concentration was measured using Potensiometer spesific ion fluoride on Laboratory Batan Yogjakarta. The result showed there was an influenced of transport test on group I and II (Anova significanve  0,000 and 0,00). While on control group found there was no influenced (Sig 0.07). Donor solution with NaF added by enhancer showed the highest penetrating power compared to group NaF solution.